Development of Dual Intake Port Technology in ORC-Based Power Unit Driven by Solar-Assisted Reservoir - Fabio Fatigati; Roberto Cipollone (Energies, 2024)
The ORC-based micro-cogeneration systems exploiting a solar source to generate electricity and domestic hot water (DHW) simultaneously are a promising solution to reduce CO2 emissions in the residential sector. In recent years, a huge amount of attention was focused on the development of a technological solution allowing improved performance of solar ORC-based systems frequently working under off-design conditions due to the intermittence of the solar source availability and to the variability in domestic hot water demand. The optimization efforts are focused on the improvement of component technology and plant architecture. The expander is retained as the key component of such micro-cogeneration units. Generally, volumetric machines are adopted thanks to their better capability to deal with severe off-design conditions. Among the volumetric expanders, scroll machines are one of the best candidates thanks to their reliability and to their flexibility in managing two-phase working fluid. Their good efficiency adds further interest to place them among the best candidate machines to be considered. Nevertheless, similarly to other volumetric expanders, an additional research effort is needed toward efficiency improvement. The fixed built-in volume ratio, in fact, could produce an unsteady under- or over-expansion during vane filling and emptying, mainly when the operating conditions depart from the designed ones. To overcome this phenomenon, a dual intake port (DIP) technology was also introduced for the scroll expander. Such technology allows widening the angular extension of the intake phase, thus adapting the ratio between the intake and exhaust volume (so called built-in volume ratio) to the operating condition. Moreover, DIP technology allows increasing the permeability of the machine, ensuring a resulting higher mass flow rate for a given pressure difference at the expander side. On the other hand, for a given mass flow rate, the expander intake pressure diminishes with a positive benefit on scroll efficiency. DIP benefits were already proven experimentally and theoretically in previous works by the authors for Sliding Rotary Vane Expanders (SVRE). In the present paper, the impact of the DIP technology was assessed in a solar-assisted ORC-based micro-cogeneration system operating with scroll expanders and being characterized by reduced power (hundreds of W). It was found that the DIP Scroll allows elaboration of a 32% higher mass flow rate for a given pressure difference between intake and expander sides for the application at hand. This leads to an average power increase of 10% and to an improvement of up to 5% of the expander mechanical efficiency. Such results are particularly interesting for micro-cogeneration ORC-based units that are solar-assisted. Indeed, the high variability of hot source and DHW demand makes the operation of the DIP expander at a wide range of operating conditions. The experimental activity conducted confirms the suitability of the DIP expander to exploit as much as possible the thermal power available from a hot source even when at variable temperatures during operation.